ANALISIS RASIO PROFITABILITAS BANK MUAMALAT INDONESIA TAHUN 2010 – 2019 - Yusanti Reska; Widayatsari Any; Kornita Endang Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the Profitability Ratios of Bank Muamalat Indonesia in 2010 - 2019. The type of data used in this study is secondary data in the form of time series obtained from the financial statements of Bank Muamalat Indonesia for 2010 - 2019. The data analysis method used in this study namely horizontal analysis. The condition of Bank Muamalat Indonesia is very worrying, seen from the declining ROA value throughout the year, where Bank Muamalat Indonesia cannot generate large profits. What happened was that the profit generated by Bank Muamalat decreased from year to year. The peak is that Bank Muamalat in 2019 was only able to generate a profit of 26 trillion rupiah. This condition is considered that Bank Muamalat is low in anticipating losses and in increasing capital. Likewise with ROE, the ability of the bank's paid-in capital to generate low profits, where the return on equity of Bank Muamalat tends to decrease every year. This shows that the rate of return on capital received by investors or invested capital is very small. So that it makes investors not interested in entering Bank Muamalat As with REO, Bank Muamalat Indonesia's REO also experiences a decline every year. Every operational expense issued by Bank Muamalat, the bank is unable to balance it with its operating income. Until Bank Muamalat. So basically Bank Muamalat Indonesia is experiencing problems in running its company. Because throughout the year, Bank Muamalat experienced a decline in its business. Banks are not able to compete with other banks and have lost competitiveness. Currently, Bank Muamalat needs capital to repair and revive its company from the brink of bankruptcy.Keywords: Profitabilitas, Return On Assets, Return On Equity, Rasio Efisiensi Operasional